2008
DOI: 10.1111/j.1469-8749.2008.03031.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive short‐term outcome assessment of selective dorsal rhizotomy

Abstract: This study retrospectively evaluated the safety and efficacy of selective dorsal rhizotomy (SDR) in participants who underwent a rigorous selection process, uniform surgical procedure, and a standardized postoperative rehabilitation process. Outcome measures assessed were the Ashworth scale for spasticity, the Gillette Gait Index (GGI) for overall gait pathology, oxygen cost for gait efficiency, and the Gillette Functional Assessment Questionnaire (functional walking ability scale; [FAQ]) for functional mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 29 publications
8
77
0
1
Order By: Relevance
“…A retrospective study involving 136 children with CP who underwent SDR showed a marked reduction in spasticity and improved functional mobility. The study confirmed that the procedure was safe with no long-term complications [2]. Similar excellent functional outcomes of SDR have been described by others [3].…”
supporting
confidence: 89%
“…A retrospective study involving 136 children with CP who underwent SDR showed a marked reduction in spasticity and improved functional mobility. The study confirmed that the procedure was safe with no long-term complications [2]. Similar excellent functional outcomes of SDR have been described by others [3].…”
supporting
confidence: 89%
“…While this is an important piece of work, the outcomes were based on limited 2D gait analyses. Three-dimensional gait analysis was only widely incorporated in CP research in the late 1990s, and therefore SDR follow-up studies that include 3D gait analysis have focused on short-term follow-up periods [10,23,24]. The current study appears to be the first ever published, which documents 3D gait analysis status of patients with spastic diplegia more than 17 years after SDR.…”
Section: Discussionmentioning
confidence: 82%
“…The current study appears to be the first ever published, which documents 3D gait analysis status of patients with spastic diplegia more than 17 years after SDR. The combination of these outcomes with the 20 year 2D gait followup study [16], and short-term (on average 10-20 months) 3D follow-up studies of other research groups [10,23,24] results in novel invaluable information for guidance in treatment decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Control and the pattern of motor disorder resulting from the upper motor neurone lesion can often be inferred from the variability of the gait pattern from step to step as shown in the consistency plot [44]. Typically whilst the pattern may not be normal, a child with relatively good control but bad spasticity will have a very consistent gait pattern from step to step.…”
Section: Patient Selectionmentioning
confidence: 99%
“…In two papers from Gillette Children's Specialty Healthcare the effect of selective dorsal rhizotomy in isolation [44] and as part of an integrated programme [36] is reported. Crucially, a very rigourous and multidisciplinary selection process underpins both papers producing a highly selected group of children.…”
Section: Short Term Outcomesmentioning
confidence: 99%